2019
DOI: 10.24251/hicss.2019.525
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Factors Influencing the Intention to Use Physician Rating Websites

Abstract: Physician rating websites (PRWs) are social media platforms that enable patients to submit ratings and reviews of physicians. While numerous PRWs are available on the Internet and millions of physician reviews are posted on those websites, many people still do not use them when making clinical decisions. This study seeks to understand what factors impact intention to use PRWs. A sample of 109 students was employed. Each subject was randomly assigned to either RateMDs, Vitals, or Brigham and Women's Hospital's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…A system higher in the perceived IH offers a positive user-performance relationship. Scholars also suggest that perceived usefulness/IH/value is the antecedent of consumer behavior [ 57 , 58 ]. For these reasons, we propose that helpful information on a PRW leads to assist users in positively evaluating the quality of physician healthcare services, lead to positive behavior toward that physician.…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…A system higher in the perceived IH offers a positive user-performance relationship. Scholars also suggest that perceived usefulness/IH/value is the antecedent of consumer behavior [ 57 , 58 ]. For these reasons, we propose that helpful information on a PRW leads to assist users in positively evaluating the quality of physician healthcare services, lead to positive behavior toward that physician.…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…Reviews shared by users on available services do also add value to the community. It not only helps to enhance the credibility of the forum but also facilitates users to evaluate and decide from available treatment methods (Kordzadeh, 2019). There are three types of participants in an OHC.…”
Section: Participation Elementsmentioning
confidence: 99%
“…Finally, our study contributes to the emergent body of research focusing on the reasons that motivate patients to use PRWs [21,29]. Prior work that examined the role of the pleasure motive vis-à-vis cognitive and executional costs, concluded that these factors provided an incomplete view of the motivations underlying patients' postings on PRWs [21].…”
Section: Theoretical Implicationsmentioning
confidence: 92%